2015
DOI: 10.1103/physrevb.92.144503
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting gap inBaFe2(As1xPx)2from temperature-dependent transient optical reflectivity

Abstract: Temperature and fluence dependence of the 1.55-eV optical transient reflectivity in BaFe2(As1−xPx)2 was measured and analysed in the low and high excitation density limit. The effective magnitude of the superconducting gap of ∼5 meV obtained from the low-fluence-data bottleneck model fit is consistent with the ARPES results for the γ-hole Fermi surface. The superconducting-state nonthermal optical destruction energy was determined from the fluence dependent data. The in-plane optical destruction energy scales … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The first problem is how many gaps should be used for the fit. Even if a single gap amplitude of about 5 meV has been recently measured in BaFe 2 (As 1−x P x ) 2 crystals with T c ;30 K by optical transient reflectivity [44] and nanocalorimetry [14], a single-gap model is unable to fit the PCARS conductance curves in the pristine and in the irradiated films. In most cases, the curves show symmetric conductance maxima and additional shoulders at higher energy, a typical sign of (at least) two gaps.…”
Section: Determination Of the Energy Gapsmentioning
confidence: 99%
“…The first problem is how many gaps should be used for the fit. Even if a single gap amplitude of about 5 meV has been recently measured in BaFe 2 (As 1−x P x ) 2 crystals with T c ;30 K by optical transient reflectivity [44] and nanocalorimetry [14], a single-gap model is unable to fit the PCARS conductance curves in the pristine and in the irradiated films. In most cases, the curves show symmetric conductance maxima and additional shoulders at higher energy, a typical sign of (at least) two gaps.…”
Section: Determination Of the Energy Gapsmentioning
confidence: 99%
“…When T approaches T c , the gap closes and more low-energy bosons are involved for the relaxation processes, resulting in a divergence nearby T c , which can be simply described to be proportional the inverse of the gap as τ (T ) ∝ 1/∆(T ) [21]. Figure 3(a) shows a fit to τ slow in the vicinity of T c using a BCS-like T -dependent gap ∆(T ) = ∆(0) 1 − T /T c , where ∆(0) is the gap at 0 K. It has already been found that the divergence of SC/CDW QPs relaxation nearby T c is a universal feature in cuprates [19,[21][22][23][24][25][26]35], pnictides [28][29][30] and CDW systems [26,27,31].…”
Section: Discussionmentioning
confidence: 94%
“…In HTSC and charge density wave (CDW) systems, the relaxation process is bottlenecked by the presence of the charge gaps when the photoexcited QPs relax to states near the Fermi level. Subsequently, the photoexcited QPs recombine by the emission and reabsorption of bosons with energy greater than 2∆ [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Therefore this method allows to directly distinguish the gap character by tracking relaxation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The fit-resulted gap size of 𝛥 s ≃ 4.7 meV is consistent with the gap size on the hole Fermi surfaces of ∼ 5 meV observed in the ARPES experiment and in the optical transient reflectivity measurement on BaFe2(As0.7P0.3)2 single crystals. [26,44] Specifically, according to the ARPES experiment, for the 𝛽 and 𝛾 bands of hole FSs, the gap energies are 5-8 meV and are nearly isotropic on the entire hole FSs. On the contrary, a strong anisotropy in the SC gap was found on electron-like FSs.…”
mentioning
confidence: 99%